Discussion on TCM Syndrome Differentiation and Treatment of Pulmonary Interstitial Fibrosis based on Liu Huawei’s Five Elements Gasification Theory - Lu, Shuai; Ma, Zhanping (Journal of Contemporary Medical Practice, 2026)
Pulmonary interstitial fibrosis is a common and difficult disease of respiratory system, which belongs to the category of interstitial lung disease. At present, the global incidence rate is about 0. 09–1. 30/10000, and it is increasing year by year. There is no effective treatment in modern medicine. Lung transplantation is often performed after the complete loss of lung function. The operation cost is high and the medical burden is heavy. Traditional Chinese medicine has rich experience and unique advantages in treating this disease. On the basis of inheriting the predecessors, Professor Liu Huawei created the theory of five elements Zang Fu Qi machine gasification (referred to as “five elements gasification theory”), which has achieved good clinical effect. Guided by this theory, this paper systematically expounds the TCM syndrome differentiation and treatment rules of pulmonary interstitial fibrosis. Through the analysis of the etiology, pathogenesis and syndrome evolution law of the disease, the basic pathogenesis of the disease is the deficiency of lung qi (Yin), the loss of Qi, phlegm dampness and blood stasis, and the imbalance of Qi mechanism, which belongs to the syndrome of excess due to deficiency, deficiency due to excess, and the mixture of deficiency and excess. On this basis, the six syndrome types of qi deficiency and phlegm stagnation, upper excess and lower deficiency, Qi deficiency and blood obstruction, lung stomach qi inversion, lung kidney yin deficiency, spleen kidney yang deficiency were summarized, and the basic treatment method of “strengthening vital energy to replenish lung and spleen, promoting gasification to expel phlegm and blood stasis” was established, and the representative prescriptions were given respectively. For the early asymptomatic patients, the idea of disease differentiation and treatment was put forward, which was mainly composed of Maiwei Buzhong Yiqi Decoction and Qianjin Weigan decoction. In order to provide new ideas and methods for TCM clinical diagnosis and treatment of pulmonary interstitial fibrosis, this paper preliminarily constructed the syndrome differentiation and treatment system of pulmonary interstitial fibrosis under the guidance of the five element theory of gasification.